Male Teachers' Perceptions of Motivation to Become PAUD Teachers in Alak District, Kupang City - Nona Hindri Yanti Manggoa; Kristin Margiani; Engelbertus Nggalu Bali (Early Childhood Education Development and Studies (ECEDS), 2023)
This research aims to determine "male teachers' perceptions of motivation to become PAUD teachers in Alak District, Kupang City". The method used in this research is descriptive qualitative. The research subjects used were male teachers who actively taught at PAUD institutions. Data collection techniques use interview techniques. The results of the research conducted show that the male teacher's perception of the motivation of a male teacher to become a PAUD teacher is due to his inner calling and love of children, receiving support from the principal and colleagues who have given him their trust to dedicate themselves. in PAUD institutions, in line with this, male teachers realize that the presence of a male figure in PAUD institutions is a substitute for a father figure, and the closeness between male teachers and early childhood children is very close, because the children are comfortable and enjoys playing with male teachers.